Mentoring Person-Centered Spiritual Maturation: A Quasi-Experimental Mixed Methods Study of a Contemplative Self-Inquiry Curriculum. (October 2015) - Kass, Jared D.; Baxter, Jonathan; Lennox, Susan
Person-centered spiritual maturation is a developmental process with prosocial potential for individuals and communities with diverse belief systems (including secular humanism). Investigation of this process has historical roots in Kass's work with Dr. Carl Rogers on the Person-Centered Approach Project. Previous work identifies this construct's conceptual properties. This article reports the effectiveness of a curriculum to mentor this learning process in higher education. We conducted a quasi-experimental, mixed methods study (triangulated qualitative and quantitative data) with experimental and control groups. Qualitative analysis (written student narratives, experimental group) documented five dimensions of growth (behavioral, cognitive, social–emotional, contemplative, and integrative) that culminated in a resilient worldview and prosocial behavior. Statistical analysis (experimental and control groups, pre–post intervention) confirmed these findings, demonstrating significant improvement in quantifiable elements of person-centered spiritual maturation. Effect sizes were meaningful, indicating 15% to 21% greater improvement in the experimental group. These results suggest that person-centered spiritual maturation can serve as a prevention-oriented, community-building intervention for higher education. It offers an integrative model of learning through which faculty in the social sciences and other disciplines can mentor social–emotional growth and contemplative self-inquiry, helping university communities build sustainable cultures of health, social justice, and peace. Further research is necessary and justified.